Heavy metal pollution simplifies microbial networks and enhances modularity during tailings primary succession: divergent assembly dynamics for bacterial and fungal communities - Li, Min; Liu, Jun; Cao, Dan; Chen, Xueyi; Shi, Jiaxin; Hu, Wenzhe; Xiao, Chunqiao; Fang, Yun (Frontiers in Microbiology, 2025)
Microbial community play a fundamental role in primary succession of tailings ecosystems. However, the influence of heavy metal pollution on microbial interactions and assembly dynamics during this process remains poorly understood. In this study, we investigated bacterial and fungal communities in tailing soil and biological soil crusts (BSCs) undergoing primary succession under varying heavy metal pollution. By integrating microbial community profiling with measurements of soil nutrients and heavy metal concentrations, we aimed to elucidate how pollution levels shape microbial composition, co-occurrence networks, and assembly processes. Our results revealed clear differences in soil physicochemical properties, microbial diversity, community structure, and ecological interactions between low and high pollution conditions. Under high contamination, Burkholderiales dominated the bacterial communities, while Saccharomycetales and Pleosporales were representative among fungi. Microbial diversity decreased with increasing pollution, accompanied by simplified co-occurrence networks and increased modularity. In highly polluted environments, both bacterial and fungal communities exhibited stronger correlations with environmental factors. Interestingly, bacterial communities were more strongly associated with soil nutrient parameters, whereas fungal communities responded more closely to heavy metal concentrations. Community assembly analysis further showed a shift toward deterministic processes in bacterial communities under high pollution, while fungal assembly remained largely stochastic. These findings highlight the differential responses of bacterial and fungal communities to heavy metal stress and underscore the critical role of pollution in shaping microbial succession in tailing ecosystems. This study provides important insights into microbial ecology under environmental stress and may inform strategies for the bioremediation and management of contaminated mine lands.